IMPLIKATUR KALIMAT PERINTAH PADA ANIME THE QUINTESSENTIAL QUINTUPLETS (Gotoubun no Hanayome) - Pratiwi, Fatma Ayu; Aibonotika, Arza; Rahayu, Nana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research discusses about Implicature imperative sentences on the anime The Quintensential Quinttuplets (Gotoubun No Hanayome). The aim of this study was to show the imperative classification on The anime The Quintensential Quintuplets (Gotoubun No Hanayome), and describe the means-end analysis that affects on the sentence change into the implicature imperative sentence on The anime The Quintensential Quintuplets (Gotoubun No Hanayome). In this study used the theory means-end by Geoffrey Leech in 1993. The data collection techniques that used by the record and observation techniques (observation). The results of this study are 37 data implicature imperative sentences. It’s generally known the purpose of implicature imperative sentence to maintain the compassionate benefit in the conversation.Key Words: Implicature, imperative sentences , means-end, Japanese Language